2016
DOI: 10.1007/s00068-016-0676-3
|View full text |Cite
|
Sign up to set email alerts
|

Lateral compression type B 2-1 pelvic ring fractures in young patients do not require surgery

Abstract: Type B 2-1 pelvic ring fractures in young patients should be treated non-operatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 26 publications
2
25
0
1
Order By: Relevance
“…Nevertheless, there is a trend toward more operative treatment in recent years. 1 , 12 - 15 Nevertheless, for elderly patients, there is a lack of evidence for treatment strategies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, there is a trend toward more operative treatment in recent years. 1 , 12 - 15 Nevertheless, for elderly patients, there is a lack of evidence for treatment strategies.…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 11 , 12 Even in young patients, the literature is dissent about treatment strategies for lateral compression fractures. 13 - 15 For elderly patients with osteoporotic fractures, there is a paucity of data about treatment strategies to decrease comorbidity and avoid prolonged fracture healing due to osteopenia and osteoporosis. 1 , 2 , 12 Therefore, the rationale of operative surgical treatment for elderly patients is to reduce the fracture-related pain first.…”
Section: Introductionmentioning
confidence: 99%
“…Thirty-eight studies [ 8 , 9 , 25 , 26 , 28 – 30 , 32 – 36 , 10 , 37 44 , 46 , 47 , 11 , 48 54 , 56 , 18 – 22 , 24 ] used a pelvic-specific PROM, either as a single instrument or in combination with a generic PROM. Generic PROMs for physical functioning and quality of life were used in 15 studies [ 8 , 10 , 39 , 40 , 46 , 57 , 58 , 12 , 13 , 15 , 17 , 19 , 23 , 27 , 30 ]. The follow-up moment when these questionnaires were assessed ranged from six months to 15 years after the injury.…”
Section: Resultsmentioning
confidence: 99%
“…With a resolution of the ultrasound measuring system of 0.1 mm, we showed that the stabilization of the posterior pelvic ring with a minimally invasive tension banding achieves a comparable stability as a sacroiliac screw. The effect of a higher dislocation of the anterior pelvic fracture as seen in the FiberTape® group could also be seen in conservatively treated pelvic fractures type B 2.1 without any problems in bone healing of the anterior pelvic ring in patients under 65 years [31]. We therefore assume that the slightly increased dislocation at the anterior pelvic ring using tape suture for posterior pelvic ring stabilization is not clinically relevant.…”
Section: Discussionmentioning
confidence: 99%